Examining the behavior and performance of SDN-enabled VLAN in switch network - Ahmed, Mohamud Abdulkadir (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2019)
The Virtual Local Area Network (VLAN) has been around for over three decades and make use of in campus and enterprise networks as one of the most preferred systems virtualisation solution. As a result of the benefits accomplished by utilising VLAN, network operators and administrators have been using it for creating their networks until today and have even extended it to handle the networking in a cloud computing system. Moreover, VLAN is a modern technology that can set up logical networks independent of physical network framework. The outcomes of previous researches have predicted that a Virtual Network is needed, which eventually produces a VLAN. However, their configuration is a complicated, tedious, time-consuming, and error-prone process. The present network standard is not adaptable, dependence on vendors is significant because the feature of the forwarding plane (also called data plane) and control plane remain in one device bundle. While, Software-Defined Networking (SDN) seems like a feasible substitute network architecture that permits separation of information plane, as well as the control plane feature on the devices. It is a promising solution for handling the challenges mentioned above in VLAN management. In this dissertation study, the first implementation SDN-enabled VLAN by leveraging OpenFlow. Next, the study investigates the performance of SDN-Enabled VLAN with Access VLAN. Besides, the study examines the packet processing behaviour in transmission both SDN-enabled switch and conventional switch. The result of the research indicates that SDN-Enabled VLAN offers more efficient configuration, far better network performance, and also reduced latency in packet transfer between VLAN segmentation